Gotta catch ‘em all: invigorating Pokémon through an innovative brand extension - Butcher, Luke; Sung, Billy; Raynes-Goldie, K. (Palgrave Macmillan, 2018)
© 2018 Macmillan Publishers Ltd., part of Springer Nature Despite the success of similar and far more immersive games from lesser known brands, Pokémon Go burst into pop-culture by merging augmented reality technology with the much-adored Pokemon world. The strategy of (re)capturing new and old fans through a highly innovative brand extension has been successful, illustrated by the total distance walked in real life by its players through the game being further than the distance from Earth to Pluto. With the release of further AR gaming extensions from colossal brands already underway (see Star Wars’ Find The Force), how can we explain the success of Pokemon Go as an innovative gaming brand extension? Collecting data from a sample of extensive players of Pokemon Go, results yield intriguing findings into the favourable and unfavourable evaluations of the innovative extension, offering substantial insights to those seeking to expand or rejuvenate brand portfolios through innovative brand extensions.